2022
DOI: 10.3389/fbioe.2021.740712
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Matrix Derived From Dental Pulp Stem Cells Promotes Mineralization

Abstract: Background: Extracellular matrix (ECM) plays a pivotal role in many physiological processes. ECM macromolecules and associated factors differ according to tissues, impact cell differentiation, and tissue homeostasis. Dental pulp ECM may differ from other oral tissues and impact mineralization. Thus, the present study aimed to identify the matrisome of ECM proteins derived from human dental pulp stem cells (DPSCs) and its ability to regulate mineralization even in cells which do not respond to assaults by miner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 55 publications
4
13
0
Order By: Relevance
“…The hFc-treated hDPSCs dECM did not show the remaining mineral content. This observation was consistent with a previous study showing that decellularized process could eliminate the mineral content in dECM of the hDPSCs culture in the OM medium ( Nowwarote et al, 2021 ). However, in the present study, we noted that decellularization could not eliminate mineral components in Jagged-1 treated hDPSCs dECM.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The hFc-treated hDPSCs dECM did not show the remaining mineral content. This observation was consistent with a previous study showing that decellularized process could eliminate the mineral content in dECM of the hDPSCs culture in the OM medium ( Nowwarote et al, 2021 ). However, in the present study, we noted that decellularization could not eliminate mineral components in Jagged-1 treated hDPSCs dECM.…”
Section: Discussionsupporting
confidence: 93%
“…In this study, we generated and characterized the dECMs from immobilized Jagged1-treated hDPSCs and subsequently illustrated their osteoinductive activity on SCAPs. Previous reports showed that human gingival stem cells (hGSCs) could well attach, spread, and proliferate on hDPSC-derived dECMs ( Nowwarote et al, 2021 ). In addition, hDPSC-derived ECM markedly enhanced the osteogenic differentiation of hGSCs ( Nowwarote et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MatrisomeDB 2.0 also includes two new studies on the ECM of hepatic metastasis from colorectal tumors ( 54 , 55 ) and an additional dataset on the ECM of aging lung ( 56 ). Last, we included three studies reporting the composition of the ECM produced in vitro by dental pulp stem cells ( 57 ), lung fibroblasts ( 58 ) and kidney organoids ( 59 ). Importantly, this release includes, for the first time, data on the ECM of aging tissues (skin, lung, intervertebral discs).…”
Section: Resultsmentioning
confidence: 99%
“…For example, Melatonin-loaded hydrogels show favourable viscoelastic properties and promote accelerated and enhanced quality of bone formation in regeneration of furcation defect in dogs ( Abdelrasoul et al, 2022 ). Specifically, extracellular matrix derived from dental pulp stem cells can promote mineralization of human gingival fibroblasts ( Nowwarote et al, 2022 ). Dual ECM scaffolds derived from pulp and endothelial ECM promote attachments of mesenchymal stem cells and subsequently odontogenic differentiation.…”
Section: Regenerative Potential Of Extracellular Spacementioning
confidence: 99%